Food tree species selection for nutrition-sensitive forest landscape restoration in Burkina Faso - Vinceti, Barbara; Fremout, Tobias; Termote, Céline; Fallas Conejo, Diego Alberto; Thomas, Evert; Lachat, Carl; Toe, Laeticia Celine; Thiombiano, Adjima; Zerbo, Issouf; Lompo, Djingdia; Sanou, Lassina; Parkouda, Charles; et al. (Wiley, 2022)
Modern food systems push agriculture to focus on a small number of commercial crops, while there is a very large diversity of untapped edible plants that could be used to address food security and nutrition. Poor and monotonous diets are closely linked to the complex burden of multiple forms of malnutrition and dietary risk. In some contexts, such as West Africa, micronutrient deficiency risks are particularly pronounced. Hence, there is an urgent need to provide people with healthy diets supported by sustainable food systems. Within this context, using nutrition-sensitive forest landscape restoration to combat environmental degradation could contribute towards ensuring the year-round availability of nutritious tree-based food.